1997
DOI: 10.1038/sj.leu.2400619
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting complete remission in patients with hairy cell leukemia treated with 2-CdA: a 5-year survey

Abstract: 6 months after therapy, and thereafter every 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…The relapse rate, DFS and survival associated with 2-CdA in pts with HCL are not well established, because only a few studies are concerned with a longer follow-up. [5][6][7][8][9] This purine analog has dramatically improved the clinical course and prognosis of this disorder, although responsible for neutropenia and lymphocytopenia often associated with fever of unknown origin or proven infectious complications. In our analysis, we wished to address several questions with regard to a long-term follow-up evaluation: what is the long-term prognosis for pts achieving remission with 2-CdA and what is the incidence of relapse?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relapse rate, DFS and survival associated with 2-CdA in pts with HCL are not well established, because only a few studies are concerned with a longer follow-up. [5][6][7][8][9] This purine analog has dramatically improved the clinical course and prognosis of this disorder, although responsible for neutropenia and lymphocytopenia often associated with fever of unknown origin or proven infectious complications. In our analysis, we wished to address several questions with regard to a long-term follow-up evaluation: what is the long-term prognosis for pts achieving remission with 2-CdA and what is the incidence of relapse?…”
Section: Discussionmentioning
confidence: 99%
“…Following these encouraging results, several studies have reported a long-term follow-up of 3-5 years after treatment with 2-CdA. [5][6][7][8][9] In this paper, we analyze the initial and long-term results at 10 years, such as clinical outcome, duration of response, toxicity and survival of 44 HCL pts uniformly treated with a single 7-day course of 2-CdA by continuous infusion. The experience of both pretreated pts, including splenectomy, interferon a (IFN) and deoxycoformycin (dCF), as well as previously untreated pts will be described.…”
Section: Introductionmentioning
confidence: 99%
“…2 The mechanisms underlying GO resistance are incompletely understood; however, efflux of the calicheamicin moiety by P-glycoprotein (Pgp) and, to a lesser extent, multidrug resistance protein (MRP), has been implicated. 3 Breast cancer resistance protein (BCRP/ABCG2), another member of the adenosine triphosphate-binding cassette (ABC) family of transporters, is widely expressed in normal tissues, including primitive hematopoietic stem cells. Evidence to date suggests that BCRP mainly serves to protect cells from xenobiotic toxins, although additional functions in stem cell populations are discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements in treatment and outcome have been made in recent years. 2,3 The natural history of HCL is well documented and involves development of resistance to therapy. Here, we report three cases of HCL with significant number of large cells.…”
Section: To the Editormentioning
confidence: 99%
“…Like DCF, a number of studies have demonstrated the efficacy of CDA in HCL [24,26,27,31,[54][55][56][57][58][59][60][61]. Different routes and schedules of administration of CDA have been used.…”
Section: Purine Analogsmentioning
confidence: 99%